Reconstructing the origin among the descendants of naturalized voltaic immigrants Ivorians in Bouaflé: Reconstruire l’origine chez les descendants d’immigrés voltaïques naturalisés Ivoiriens à Bouaflé - Houedin, Barnabé (International Journal of Scientific Research and Management (IJSRM), 2021)
This article aims to examine the strategies of reconstruction of the "Mossi" origin among the descendants of naturalized immigrants in Bouaflé. The qualitative data obtained are the result of a series of individual and collective interviews. At the end of the study, it appears that the processes of reconstruction of origin appear as practices aimed on the one hand to escape the ethnic control induced by the anteriority on this reception area and on the other hand to strengthen the quests for autonomy orchestrated through the claim of native status.These practices are carried out concurrently and implicitly following units of action between naturalized villages. They also hide mechanisms aimed at enhancing the identity of native groups among the local native groups. This essentially involves symbolic and economic resources such as the legitimization of the "Mossi electorate", the strengthening of expressions of citizenship in the direction of the autonomy of naturalized villages and the appropriation of land.